Public awareness and knowledge on rabies: a survey-based analysis - Gloria Daniel, Twinkle; Pattnaik, Shweta; Tiwari, Priyanka; Nand, Ankit; Solomon, Eunice; Rahangdale, Yogita (International Journal Of Community Medicine And Public Health, 2026)
Background: Rabies is a fatal yet preventable viral disease that attacks the central nervous system and is endemic in more than 150 countries. Despite advancements in vaccines and treatments, rabies remains a neglected tropical disease. Therefore, present study aims to assess the awareness and knowledge about rabies among general population. Methods: Quantitative descriptive cross-sectional survey research design was used to conduct the study. A sample of 567 participants from general population was selected for the study using random sampling technique from social media platform across India. Results: Study revealed that overall, 68.43% participants were aware about transmission of rabies, 48.68% participants were knowledgeable about symptoms of rabies and 69.49% participants had knowledge about preventive measures about rabies. There was no significant association found between awareness regarding transmission of rabies, symptoms of rabies and preventive measures of rabies with any of demographic variables of the participants Conclusions: Study concluded that there was a mild to moderate level of knowledge among general population. Hence, proper awareness regarding various rabies diseases and its prevention can help in reducing such risk among general population.